SUPERVISI KEPALA MADRASAH SEBAGAI UPAYA MENINGKATKAN PROFESIONALISME GURU DI MA DARUL FALAH KECAMATAN DIWEK KAB JOMBANG TAHUN PELAJARAN 2014/2015 - Ubaidillah, - (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Abstract: This study was conducted to investigate the implementation of supervision carriedout by the headmaster at Darul Falah MA Diwek District of Jombang. Issues raised are: 1. How is the implementation of supervision headmaster in MA Darul Falah District of Diwek Jombang? 2. What are the problems faced in the implementation of supervision headmaster in MA Darul Falah District of Diwek Jombang? 3. What measures are taken to address the problems of supervision headmaster in MA Darul Falah District of Diwek Jombang? 4. What is the pattern of supervision headmaster in MA Darul Falah District of Diwek Jombang?This research use desciptive qualitative approach. In a study with qualitative approaches,collecting data using interviews, observation and documentation. Analysis and interpretation of the data is the stage that must be passed by a researcher within the scope of his research. As for the order after the data collection phase, the data used in the analysis of qualitative research in the form of interactive analysis (interactive analysis). The results were: 1) Implementation of supervision headmaster at Darul Falah MA Diwek Jombang District of running quite smoothly principal matters that received supervision by the headmaster is with regard to the learning aspect, administration. 2) The problems encountered in the implementation of the supervision of the head of MA Darul FalahDistrict of Diwek Jombang is the complexity of the managerial duties of a headmaster, lack of preparation of the teacher who supervised, element of subjectivity teacher supervisor is still considered high and frequent change of headmaster 3) Efforts taken to resolve the problems of supervision headmaster in MA Darul Falah District of Diwek Jombang is with the delegation of authority by the headmaster to senior teachers, Giving motivation to teachers the importance of supervision of education, coaching by the headmaster to senior teachers 4) Pattern supervision headmaster in MA Darul Falah District of Diwek Jombang is educational supervision implemented by headmaster rests on the principles of supervision that is constructive, realistic, democratic, not authoritarian, cooperative, and objectiveKeywords: Supervision Principals, teachers' professionalism